Comparing lateral flow testing with a rapid RT‐PCR method for SARS‐CoV‐2 detection in the United Kingdom—A retrospective diagnostic accuracy study. Issue 5 (14th September 2022) - Taylor, Andrew; Calvez, Ronan; Atkins, Mark; Fink, Colin G.
Abstract: Background and Aims: In late 2019, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) emerged in Wuhan, China. Rapid global spread led to the coronavirus disease 2019 (Covid‐19) pandemic. Accurate detection of SARS‐CoV‐2 has become a vitally important tool in controlling the spread of the virus. Lateral flow devices (LFDs) offer the potential advantage of speed and on‐site testing. The sensitivity of these devices compared to reverse transcription‐polymerase chain reaction (RT‐PCR) has been questioned. Methods: We compared the sensitivity of the Innova LFD, used widely in the United Kingdom, with our rapid RT‐PCR method using stored positive samples. Samples with a range of viral loads (original Ct values 18.9–36.5) were tested. Results: The Innova LFD was found to be 6000–10, 000 times less sensitive than RT‐PCR for SARS‐CoV‐2 detection. Overall, the LFD detected 46.2% of the positives detected by RT‐PCR, with 50% of these observed to be weak LFD positives. At lower viral loads, such as 10, 000–100, 000 RNA copies/ml, the LFD detected 22.2% of positives. In addition, two strong positives (3 and 1.5 million RNA copies/ml) were not detected by the LFD. Conclusion: The argument for use of LFD kits is that they detect infectious virus and hence contagious individuals. However, there is a lack of conclusive evidence supporting this claim. The Innova LFD has been subject to a Class I recall by the US Food and Drug Administration,  but is still approved and widely used in the United Kingdom.